PENGARUH KREDIT BERMASALAH TERHADAP LIKUIDITAS DAN PROFITABILITAS PADA KOPERASI ARTA MAKMUR DI REJOSO NGANJUK - Wahyu Dwi Arti Lestari; Muhammad Imron; Mutmainah (Universitas Merdeka Madiun, 2024)
This research aims to examine the effect of non-performing loans consisting of substandard loans, doubtful loans and bad loans on liquidity and profitability. The sampling technique uses the quota sample method. Data was obtained from secondary data from the monthly report of the Arta Makmur Rejoso Nganjuk Cooperative with canonical correlation with the SPSS version 25 program. The canonical weight shows the highest variable results, namely bad credit 1.08872 and profitability 0.88710. The canonical loadings show the highest variable results, namely bad credit 0.95348; liquidity 0.94779 and profitability 0.99907. Canonical cross-loading shows the highest variable results, namely substandard credit 0.65801; bad debt 4.21658 and profitability 4.09189. The results of the hypothesis research show that the variable that has no influence is doubtful credit. From the results of canonical weights, canonical loadings and canonical cross-loading, it can be concluded that there is no significant influence between substandard credit and liquidity. There is no significant influence between doubtful credit and liquidity. There is a significant influence between bad credit and liquidity. There is a significant influence between substandard credit on profitability. There is no significant influence between doubtful credit on profitability. There is a significant influence between bad credit and profitability. There is a significant influence between non-performing loans on liquidity and profitability.